## finding inverse of non-linear transformation

Find the inverse of the (nonlinear) transformation from R^2 to R^2 given by

u=3y
v=3x^7-6y

x=?
y=?

3. The attempt at a solution

- I'm really not sure what to do on this problem. We haven't seen any problems even similar to it in class, so I'm looking for help on it.
 PhysOrg.com science news on PhysOrg.com >> Galaxies fed by funnels of fuel>> The better to see you with: Scientists build record-setting metamaterial flat lens>> Google eyes emerging markets networks

Recognitions:
Gold Member
Staff Emeritus
 Quote by snoggerT Find the inverse of the (nonlinear) transformation from R^2 to R^2 given by u=3y v=3x^7-6y

So y= u/3. Put that into the second equation: v= 3x^7- 6(u/3)= 3x^7- 2u.
Solve that for x.

 x=? y=?
 3. The attempt at a solution - I'm really not sure what to do on this problem. We haven't seen any problems even similar to it in class, so I'm looking for help on it.
 well, that was much easier than I thought it would be. Can you explain to me why that is the inverse?

Recognitions:
Gold Member